Pemodelan Debit Menggunakan Metode Arima Guna Menentukan Pola Operasi Waduk Selorejo - Pramujo, Bambang; Juwono, Pitojo Tri; Soetopo, Widandi (Fakultas Teknik, Universitas Brawijaya, 2014)
Selorejo dam is located in the village of Pandansari, Ngantang Sub Regency, Malang Regency. It is located in Kali Konto, a tributary of the Brantas River. Selorejo dam has a very important function, especially for the purposes of hydroelectric power generation and irrigation. As an old dam, completed in 1970, Selorejo experiences a decreasing volume of its reservoir due to a high sedimentation rate. The decreasing volume Selorejo reservoir has impacted the function of the dam and it is important to formulate a better operating rule to optimalize the current volume. During the planning of the operating rule of Selorejo reservoir, Perum Jasa Tirta I as an operator of the Selorejo Dam use a dependable discharge in predicting inflow discharge. This study predict the inflow discharge using ARIMA forecasting method, which then used to formulate a new operating rule. This study used 10 years of 10 days period inflow discharge data, which 9 years of it used to generating the ARIMA model and the last 1-year data for calibration. The study result suggest that the best ARIMA model in predicting the dam’s inflow discharge is ARIMA (1,1,1)(2,1,1) 36. Compare to a current method, this model is proved predicts better inflow discharge which has smaller Relative Error (KR) to the real data (Model’s KR 5.5 and Operator’s KR 17.8).Keywords: ARIMA, inflow discharge, the operating rule of reservoir, reservoir of Selorejo Dam.